(untitled) (Altre Modernità, 2019)
Passages is a book about journeys: mythic, realistic journeys that bring people from one place to another, from one universe to another one. In this sense, all the characters are immigrants and/or exiles, moving through three different places: a Caribbean island (Haiti), Miami and Montreal. The aim of this essay is to introduce a non-specialist reader to the main themes of Ollivier’s novel which stands on migration, identity and home.